Childhood cancers in a tertiary facility in Southern Nigeria: a four-year update - Bassey, Eno-Obong U.; Udo, Ekemini Nsikan (International Journal of Research in Medical Sciences, 2022)
Background: Cancer is a global epidemic and leading cause of death for children and adolescents worldwide. Developing countries contribute an estimated 60-80% of the total burden of all new cancer cases worldwide. Data on the burden of childhood cancers across Nigeria varies from centre to centre and may well even vary in periodic reviews done in the same areas over a time lag. It was therefore important to have periodic reviews of the various cancer types seen or evolving in various geographical areas. Methods: A prospective hospital-based study, over a period of four years, from January 2016 to December 2019. Children admitted and diagnosed with cancers in the paediatric medical ward of the University of Uyo Teaching Hospital were reviewed. This teaching hospital was one of the two tertiary health care facilities in the state and caters for children from different parts of the state and its environs. Results: The frequency distribution of each childhood cancer showed nephroblastoma as the predominant cancer seen, 12 (23.1%), followed by non-Hodgkin’s lymphoma, 6 (11.5%). Retinoblastoma, Burkitt’s lymphoma and Hodgkin’s lymphoma were 5 (9.1%) and ranked third respectively. Leukaemia ranked 4th in frequency; 4 (7.7%), children less than five years of age formed a greater percentage of those presenting with various cancers. Conclusions: Nephroblastoma was the predominant childhood cancer now seen in this geographical area of south-South Nigeria, with a decline in the incidence of Burkitt’s lymphoma, which was most frequent in erstwhile years.